Comparison of the Overcharge Behaviors of Lithium-ion Batteries Under Different Test Conditions. (February 2019) - Ren, Dongsheng; Feng, Xuning; Lu, Languang; Li, Jianqiu; Ouyang, Minggao
Abstract: Overcharge is one of the most severe safety issues of lithium-ion batteries. In this paper, the overcharge performance of a commercial lithium-ion battery is evaluated under different test conditions, considering the effects of charging current, restraining plate and heat dissipation. Charging current and heat dissipation are found to have only minor influence on the battery overcharge behaviors, while batteries with restraining plate and cuts on the pouches show improved overcharge performance, as SOCTR and T TR both increase significantly. Further analysis on T TR helps to identify the overcharge-induced thermal runaway mechanism for the batteries with different configurations.